Предмет: Алгебра,
автор: pelagiyazh
Упростите выражения:
tg^2x+sin^2x+cos^2x=
(sinx+cosx)^2+(sinx-cosx)^2-3
(3sin^2x+cos^4x)/(1+sin^2x+sin^4x)
Ответы
Автор ответа:
0
1) tg²x+sin²x+cos²x=tg²x+1=1/cos²x
2) (sinx+cosx)²+(sinx-cosx)²-3=sin²x+2sinx·cosx+cos²x+sin²x-2sinx·cosx+cos²x-3=2-3=-1
3) (3sin²x+cos⁴4x)/(1+sin²x+sin⁴4x)=(3sin²x+(cos²x)²/(1+sin²x+sin⁴x)=(3sin²x+(1-sin²x)²)/(1+sin²x+sin⁴x)=
=(3sin²x+1-2sin²x+sin⁴x)/(1+sin²x+sin⁴x)=1
2) (sinx+cosx)²+(sinx-cosx)²-3=sin²x+2sinx·cosx+cos²x+sin²x-2sinx·cosx+cos²x-3=2-3=-1
3) (3sin²x+cos⁴4x)/(1+sin²x+sin⁴4x)=(3sin²x+(cos²x)²/(1+sin²x+sin⁴x)=(3sin²x+(1-sin²x)²)/(1+sin²x+sin⁴x)=
=(3sin²x+1-2sin²x+sin⁴x)/(1+sin²x+sin⁴x)=1
Похожие вопросы
Предмет: Геометрия,
автор: hehivos229
Предмет: История,
автор: topokot1010
Предмет: Другие предметы,
автор: pustovalovaelizaveta
Предмет: Математика,
автор: hjvfkj
Предмет: Алгебра,
автор: Dasha81099